ANALISIS KUALITAS LAYANAN PADA WEBSITE INVITEES TERHADAP KEPUASAN PENGGUNA MENGGUNAKAN METODE SERVQUAL - Evelyn Winny Thody; Sudirman; Renny (KHARISMA Tech, 2022)
This study aims to determine the level of each dimension of service quality measurement on the Invitees website on user satisfaction. The method used in this study is the SERVQUAL method which is used to measure the level of service quality by looking for the value of the gap between expectations and perceptions of service users. The SERVQUAL method has five measurement dimensions, Tangibles, Reliability, Responsiveness, Assurance, and Empathy, but this study uses modified dimensions, namely Usability, Information Quality, Service Reliabilty, Assurance, and Empathy. The results obtained from the measurement of the five dimensions are that Usability dimension has a gap of -0.34, the Information Quality dimension has a gap of -0.19, the Service Reliability dimension has a gap of -0.19, the Assurance dimension has a gap of -0.64, and the Empathy dimension has a gap of - 0.59. Because the measurement results of all dimensions are in the negative value range, it is concluded that the service quality of the Invitees website is still not in accordance with user satisfaction.